Comparative Neuronal Differentiation of Self-Renewing Neural Progenitor Cell Lines Obtained from Human Induced Pluripotent Stem Cells - Verpelli, Chiara; Carlessi, Luigi; Bechi, Giulia; Fusar Poli, Elena; Orellana, Daniel; Heise, Christopher; Franceschetti, Silvana; Mantegazza, Renato; Mantegazza, Massimo; Delia, Domenico; Sala, Carlo (Frontiers in Cellular Neuroscience, 2013)
Most human neuronal disorders are associated with genetic alterations that cause defects in neuronal development and induce precocious neurodegeneration. In order to fully characterize the molecular mechanisms underlying the onset of these devastating diseases, it is important to establish in vitro models able to recapitulate the human pathology as closely as possible. Here we compared three different differentiation protocols for obtaining functional neurons from human induced pluripotent stem cells (hiPSCs): human neural progenitors (hNPs) obtained from hiPSCs were differentiated by co-culturing them with rat primary neurons, glial cells or simply by culturing them on matrigel in neuronal differentiation medium, and the differentiation level was compared using immunofluorescence, biochemical and electrophysiological methods. We show that the differentiated neurons displayed distinct maturation properties depending on the protocol used and the faster morphological and functional maturation was obtained when hNPs were co-cultured with rat primary neurons.